Optimal charging schedule of electric vehicles using evolutionary programming to minimise costs / Hasmaini Mohamad ... [et al.] - Mohamad, Hasmaini; Md Razali, Norhasniza; Abidin, Ahmad Farid; Salim, Nur Ashida; Mat Yasin, Zuhaila (2021)
Electric vehicle technology presents new opportunities to the transportation sector and car manufacturers worldwide. However, this development is becoming a concern to utility operators when a large number of electric vehicles are charged simultaneously, which overloading might occur, especially during peak hours. This condition can affect the stability of the grid. Since electric vehicles are considered as an additional load to the power grid, a suitable charging coordination must be presented in order to optimize grid operation. This study implemented an electric vehicle charging schedule on an IEEE 33-bus residential network using evolutionary programming for optimization. Some constraints, such as power and voltage limits of the grid were taken into consideration to ensure the efficacy of the proposed optimal charging strategy. Simulation results showed the comparison between uncoordinated and coordinated charging schemes in terms of daily load curve and EV operating costs. Three case studies were analysed for coordinated charging based on different charging periods. Electric vehicle charging rate is varied in order to determine the minimum operational costs.